Multiple Identified Neurons and Peripheral Nerves Innervating the Prothoracic Defense Glands in Stick Insects Reveal Evolutionary Conserved and Novel Elements of a Chemical Defense System - Strauß, Johannes; von Bredow, Christoph-Rüdiger; von Bredow, Yvette M.; Stolz, Konrad; Trenczek, Tina E.; Lakes-Harlan, Reinhard (Frontiers in Ecology and Evolution, 2017)
The defense glands in the dorsal prothorax are an important autapomorphic trait of stick insects (Phasmatodea). Here, we study the functional anatomy and neuronal innervation of the defense glands in Anisomorpha paromalus (Westwood, 1859) (Pseudophasmatinae), a species which sprays its defense secretions when disturbed or attacked. We use a neuroanatomical approach to identify the nerves innervating the gland muscles and the motoneurons with axons in the different nerves. The defense gland is innervated by nerves originating from two segments, the subesophageal ganglion (SOG), and the prothoracic ganglion. Axonal tracing confirms the gland innervation via the anterior subesophageal nerve, and two intersegmental nerves, the posterior subesophageal nerve, and the anterior prothoracic nerve. Axonal tracing of individual nerves reveals eight identified neuron types in the subesophageal or prothoracic ganglion. The strongest innervating nerve of the gland is the anterior subesophageal nerve, which also supplies dorsal longitudinal thorax muscles (neck muscles) by separate nerve branches. Tracing of individual nerve branches reveals different sets of motoneurons innervating the defense gland (one ipsilateral and one contralateral subesophageal neuron) or the neck muscle (ventral median neurons). The ipsilateral and contralateral subesophageal neurons have no homologs in related taxa like locusts and crickets, and thus evolved within stick insects with the differentiation of the defense glands. The overall innervation pattern suggests that the longitudinal gland muscles derived from dorsal longitudinal neck muscles. In sum, the innervating nerves for dorsal longitudinal muscles are conserved in stick insects, while the neuronal control system was specialized with conserved motoneurons for the persisting neck muscles, and evolutionarily novel subesophageal and prothoracic motoneurons innervating the defense gland.